Pengaruh Kualitas Pelayanan Terhadap Kepuasan Wisatawan Di Taman Indonesia Kaya Semarang - Suhartapa Suhartapa (Universitas Bina Sarana Informatika, 2022)
ABSTRACTThe purpose of this study was to determine the effect of service quality which includes variables of reliability, responsiveness, assurance, empathy, and physical evidence on tourist satisfaction at Taman Indonesia Kaya tourism objects in Semarang.The research population is tourist visitors at Taman Indonesia Kaya Semarang. The number of research samples used were 92 respondents. Sampling used nonprobability sampling and convenience sampling methods. Data analysis used descriptive analysis and Multiple Linear Regression analysis. The study concluded that based on the t-test on the service quality variables at Taman Indonesia Kaya, it had a positive and significant effect on tourist satisfaction. The results of the F test simultaneously obtained a value of 27,668 significance floor 0.000 <0.05, indicating a significant influence between the variables of reliability, responsiveness, assurance, empathy, physical evidence on tourist satisfaction. The coefficient of determination (R²) of the five service quality variables on tourist satisfaction is 0.617, which indicates that 61.7% of tourist satisfaction is influenced by service quality, while 38.3% of tourist satisfaction is influenced by other variables outside the service quality variable. Keywords: Service Quality, Tourist Satisfaction